Soil Characteristics in Moist Tropical Forest of Sunsari District, Nepal - Gautam, Tilak Prasad; Mandal, Tej Narayan (Nepal Journal of Science and Technology, 2013)
The physico-chemical properties of soils of tropical moist forest (Charkoshe jungle) in Sunsari district of eastern Nepal were analyzed. The samples were collected during summer season from three depths: upper (0-15 cm), middle (15-30 cm) and deep (30-45 cm). They were analyzed for texture, pH, moisture, water holding capacity, organic carbon, total nitrogen, organic matter and microbial biomass carbon and nitrogen. The forest soil of upper and middle layers was loamy whereas that of deep layer was sandy loam. The pH value was lower (5.6) in upper layer than in the deep layer (6.6). The moisture content, water holding capacity, organic carbon, total nitrogen and organic matter were higher in upper layer and decreased with increasing depth. The higher level of soil nutrients in upper layer was due partly to reduction in the loss of top soil and partly to the increased supply of nutrients from the decomposed form of litter and fine roots of the forest plants. The average value of microbial biomass carbon in the soil was 676.6 μg g-¹and microbial biomass nitrogen was 59.0 μg g-¹. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 35-40 DOI: http://dx.doi.org/10.3126/njst.v14i1.8876